Digital trade barriers and export performance: Evidence from China. (26th March 2022) - Jiang, Lingduo; Liu, Shuangshuang; Zhang, Guofeng
Abstract: This paper investigates how Chinese manufacturing exports respond to destination countries' digital trade barriers. Using Chinese Customs data from 2014 to 2018 and data on countries' digital service trade restrictiveness by the OECD, we find that Chinese total manufacturing exports drop by 2.32%, or 30.92 billion, due to the increase in destination countries' composite digital trade barriers from 2014 to 2018. A further decomposition shows that the reduction is mostly explained by the decrease in export quantity, with export prices remaining relatively unchanged. Moreover, digital trade barriers decrease Chinese exports not only by depressing the exports of surviving products but also by reducing the exporting possibility of new entering products and increasing the risk of products' exiting. The heterogeneity analyses show that a favorable institutional environment helps alleviate the negative effects and that exports of high‐tech products are less sensitive to digital trade barriers.